The Role of Rontek Gugah Sahur Art in the Formation of Collective Identity in Pacitan Society - Puspita, Nindya Dwi; Hafizhah, Nasywa Aida; Assyifa, Yumnaa; Arifin, Afriza Animawan (Universitas Muhammadiyah Surakarta, 2025)
Amid the currents of globalization that threaten the existence of local traditions, examining the role of art in shaping collective identity becomes essential to understanding the psychological mechanisms of Indonesian. society in building social cohesion. This study aims to explore how the art of Rontek Gugah Sahur contributes to the formation of collective identity among the Pacitan community through the perspective of indigenous psychology. Descriptive qualitative methods were used with three participants selected using purposive techniques, consisting of two players and one audience who had been actively following the tradition for at least 5 years. Data were collected through group interviews and analyzed using thematic analysis. The results show three main themes: (1) Rontek as a marker of cultural identity; (2) Rontek as a collective flow space; (3) Rontek as a medium for intergenerational transmission of local values. These findings are supported by Stuart Hall's theory of cultural identity, Csikszentmihalyi's flow theory, and Sawyer's group flow concept. The study concludes that Rontek significantly contributes to the development of a dynamic and adaptive collective identity, emphasizing the importance of an indigenous psychology approach in understanding Indonesian cultural phenomena.